UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MEDIA VOKUBASA PADA KELAS 5 TAHUN PEMBELAJARAN 2024/2025 DI SDN PURWOREJO - Hermawan Susanto; Rian Arya Wijaya, Melik Budiarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This classroom action research aims to improve the mathematics learning outcomes of fifth-grade students at SDN Purworejo in the academic year 2024/2025, particularly on the topic of cube and cuboid volume, through the use of VOKUBASA media (Volume Kubus dan Balok Satuan). The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 15 students. Data collection techniques included tests, observation, interviews, and documentation. The findings showed a significant improvement in students' cognitive learning outcomes after the use of VOKUBASA media. In the pre-cycle stage, none of the students achieved the Minimum Completeness Criteria (KKM). However, by the end of the second cycle, the average score had increased, and most students exceeded the KKM. The use of VOKUBASA manipulable, visual mediamade abstract mathematical concepts more concrete and easier for students to understand. The media also increased student engagement and learning motivation. In conclusion, the application of VOKUBASA media in mathematics instruction effectively improves student learning outcomes in understanding volume concepts of cubes and cuboids.